Pengaruh Kepemimpinan Dan Budaya Organisasi Terhadap Prestasi Kerja Pegawai Pada Kantor Kecamatan Sibolga Kota, Kota Sibolga - Silvia Amri Pasaribu (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2026)
This study was conducted to determine whether leadership and organizational culture influence employee performance at the Sibolga City District Office, Sibolga City. The type of research employed is causal-associative with data presented quantitatively. The results indicate that the correlation strength between Variable X1 (Leadership) and Variable X2 (Organizational Culture) with Variable Y (Employee Performance) at the Sibolga City District Office are 0.716 and 0.732, respectively, which are considered very strong. The coefficient of determination (adjusted R²) for the combined effect of X1 (Leadership) and X2 (Organizational Culture) on Y (Employee Performance) is 0.683 (68.3%), while the remaining 31.7% is explained by other factors not addressed in this study. The significance values for Leadership (X1) and Organizational Culture (X2) on Employee Performance (Y) are 4.262 and 4.551, respectively, which are greater than the t-table value of 2.0345. Therefore, since the calculated t-values exceed the t-table values, it can be concluded that both Leadership and Organizational Culture have a positive and significant partial effect on Employee Performance.